Ideal Policy Dynamics of Collection of Fees on Acquisition of Land and Building Rights on Acquisition of Land Redistribution Certificates - Priyambodo, Dimas; Dinda, Garin; Fikri, Muhammad Adymas Hikal (Fakultas Hukum Universitas Islam Jakarta, 2024)
The government tries to realize social justice and community empowerment through land redistribution initiatives. However, its implementation has several obstacles, especially in collecting the Tax on Acquisition of Land and Building Rights (BPHTB). This paper will discuss the complexity of BPHTB in relation to land redistribution initiatives. This study uses a normative juridical research methodology and a conceptual framework derived from a review of legislation. The research findings show that the main obstacle for land recipients in the redistribution scheme is BPHTB. Recipients of redistributed land, who are generally people with low-income levels, often find it financially difficult to pay the BPHTB. Regulatory changes that support land recipients in obtaining land certificates without the financial burden of BPHTB can increase the success of the land redistribution program and support the government's social justice agenda. Recommendation, there needs to be a collaboration between the Ministry of Agrarian Affairs and Spatial Planning and related parties to revise the BPHTB regulation. Certain measures that consider the economic conditions of land recipients should be implemented to ensure that the land redistribution program runs smoothly and benefits the community.